In vitro evaluation of the optimal degree of oversizing of thoracic endografts in prosthetic landing areas: a pilot study - Carlota F. Prendes, MD, FEBVS; Maximilian Grab, PhD Candidate; Jan Stana, PhD; Ryan Gouveia E Melo, MD; Aldin Mehmedovic, MD; Linda Grefen, PhD Candidate; Nikolaos Tsilimparis, PhD, FEBVS (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Objective: The optimal degree of proximal thoracic endograft oversizing when aiming for durable sealing in prosthetic grafts is unknown. The aim of the present study was to create an in vitro model for testing different oversized thoracic endografts in a reproducible and standardized manner and, subsequently, determine the optimal oversizing range when planning procedures with a proximal landing in prosthetic zones in the descending thoracic aorta or aortic arch. Methods: An in vitro model consisting of a fixed 24-mm polyethylene terephthalate (Dacron; DuPont) graft sutured proximally and distally to two specifically designed 40-mm rings, with four force sensing resistors attached at four equally distant positions and a USB camera attached proximally for photographic and video documentation was used for deployment of Zenith TX2 (Cook Medical Inc) dissection platform endografts with diameters between 24 and 36 mm. After deployment, ballooning with a 32-mm compliant balloon was performed to simulate real-life conditions. The assessment of oversizing included visual inspection, calculation of the valley areas created between the prosthetic wall and the stent graft fabric, distance between the stent graft peaks, the radial force exerted by the proximal sealing stent, and the pull-out force necessary for endograft extraction. Results: A total of 70 endografts were deployed with the oversizing ranging from 0% to 50%: 10 × 24 mm, 10 × 26 mm, 10 × 28 mm, 10 × 30 mm, 10 × 32 mm, 10 × 34 mm, and 10 × 36 mm. Two cases of infolding occurred with 50% oversizing. The valley areas increased from 8.79 ± 0.23 mm2 with 16.7% oversizing to 14.26 ± 0.45 mm2 with 50% oversizing (P < .001). A significant difference was found in the pull-out force required for endografts with <10% oversizing vs ≥10% oversizing (P < .001). The difference reached a plateau at ∼4 N with oversizing of >15%. The mean radial force of the proximal sealing stent was greater after remodeling with a compliant balloon (0.55 ± 0.02 N vs 0.60 ± 0.02 N after ballooning; P < .001). However, greater oversizing did not lead to an increase in the radial force exerted by the proximal sealing stent. Conclusions: The findings from the present study offer additional insight into the mechanics of oversized stent grafts in surgical grafts. In endografts with the Zenith stent design (TX2), oversizing of <16.7% resulted in reduced resistance to displacement forces, and oversizing of >50% was associated with major infolding in 20% of cases. Long-term in vitro and in vivo testing is required to understand how these mechanical properties affect the clinical outcomes of oversizing. : Clinical Relevance: A paucity of data is available regarding the optimal thoracic endograft oversizing that should be used when landing proximally in prosthetic grafts located in the descending thoracic aortic or aortic arch. The present study is one of the first to attempt to establish a definition of optimal oversizing for in vitro studies. It is also one of the few studies to specifically consider this subcohort of patients with complex aortic disease. Evidence from the present study suggests using oversizing of 20% to 30% for proximal sealing in prosthetic grafts. The results showed low pull-out force requirements for endografts with <16.7% oversizing but worse wall apposition for endografts with ≥30% oversizing.